Development of a strategic prioritisation model for green supply chain improvement initiatives in manufacturing industry / Seyedeh Maryam Masoumi Katesari - Katesari, Seyedeh Maryam Masoumi (2015)
The shift from reactive and compliance-based to proactive and strategic environmental management has driven companies to consider the strategic factors while identifying the areas in which they should focus their green initiatives. Meanwhile, because of the increased competition and globalisation, the scope of environmental activities is extending towards the whole supply chain. In this respect, researchers and practitioners have presented various green initiatives from the supply of raw material, through the production processes, to product consumption and end-of-life product recovery. However, in previous studies little attention was given to providing the managers with a basis from which they could strategically prioritise these green initiatives. Considering this lacuna in the literature, this research aims to develop a decision-making method for prioritising green strategies and green supply chain initiatives for the manufacturing companies. The institutional theory perspective and a natural-resource-based view are used to identify and cluster the internal and external strategic factors affecting the green strategy adoption. In addition, a broad taxonomy of green supply chain initiatives is used to cluster the list of environmental practices commonly adopted by the manufacturing industry. The causal relationship between the strategic decision factors, green strategies and green supply chain initiatives is then conceptualized to construct the decision model. This conceptual model is validated based on the results of structural equation modelling, using a dataset collected from a survey of the ISO 14000 certified manufacturers in Malaysia. On the basis of the validated decision model, the research then proceeds with proposing the prioritisation method. The techniques of analytic network process and importance performance analysis are applied to develop the final strategic prioritisation method. Software is developed to facilitate the implementation of the method by practitioners. The usability of the method is evaluated by using five real case studies from the automotive, and electric and electronic industries. This research has bridged the fields of strategic environmental management and green supply chain management by investigating the impact of internal and external strategic factors on green strategy adoption, and verifying the mediating effect of green strategy on the relationship between these strategic factors and green supply chain initiatives. In this respect, this research has made an original contribution to knowledge. A decision support method that links the results from the survey to the analytic modelling approach is developed to strategically prioritise green supply chain initiatives. This method helps practitioners engaging in strategic environmental planning to identify the improvement opportunities in line with their firm’s strategic preferences. Thus, the work presented in this study makes an original contribution to practice as well.